The effect of cobalt doping on vanadyl pyrophosphate catalyst - Taufiq-Yap, Yun Hin; Looi, Ming Hoong; Waugh, Kenneth C.; Hussein, Mohd Zobir (Springer, 2003)
Co-promoted vanadyl pyrophosphate catalyst (Co/V = 2.23%) was prepared by classical organic method via VOHPO4 · 0.5H2O precursor and calcined for 100 h in a mixture of n-butane in air. The synthesized catalyst was characterized by N2 physisorption, ICP, X-ray diffraction, scanning electron microscopy, and temperature-programmed desorption of oxygen.